Sustainability of Vegetable Hydroponic System in Pekanbaru City - Maisarah, Nadia Putri; Fariyanti, Anna; Rosiana, Nia (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The decrease in the harvested area and the reduction in horticultural land caused by the conversion of agricultural land into plantations have prompted farmers to practice vegetable farming using a hydroponic system. This study aims to analyze the level of sustainability in vegetable farming using a hydroponic system, considering various dimensions and farmers' strategies to enhance sustainable hydroponic vegetable farming in Pekanbaru City. The sustainability index was determined using the Rap-Farm Ordination Technique along with the Multidimensional Scaling (MDS) Method, Leverage Analysis, Monte Carlo Simulation, and Analytical Hierarchy Process (AHP) to analyze hydroponic vegetable farming strategies in Pekanbaru City. A saturated sample of 30 hydroponic vegetable farmers from Pekanbaru City was included in this research. The results indicate that vegetable farming using a hydroponic system exhibits a relatively high level of sustainability across different dimensions, including economic, ecological, social, institutional, and technological aspects, with a score of 64.80. The sustainability level for the fifth dimension is moderately good (economic, ecological, social, and technological), whereas the institutional dimension is highly sustainable. Therefore, attributes from the highest-value dimension (institutional) and the lowest-value dimension (social) are given priority. Consequently, these two attributes are combined to enhance the sustainability level. One crucial aspect is improving knowledge of vegetable cultivation using the hydroponic system through training programs to enhance farmers' skills. Additionally, implementing and monitoring hydroponic vegetable farming emerged as a top-ranking alternative strategy to enhance farming practices. This research is expected to assist hydroponic vegetable farmers in enhancing their sustainable farming practices. Keywords: AHP, hydroponic vegetable, Rap-Farm, sustainable farming, vegetable farming